Chromogranin A levels and mortality in patients with severe sepsis. (May 2015) - Hsu, Chih-Hsin; Reyes, Luis F.; Orihuela, Carlos J.; Buitrago, Ricardo; Anzueto, Antonio; Soni, Nilam J.; Levine, Stephanie; Peters, Jay; Hinojosa, Cecilia A.; Aliberti, Stefano; Sibila, Oriol; Rodriguez, Alejandro; et al.
Abstract Context: Chromogranin A (CgA) is a novel biomarker with potential to assess mortality risk of patients with severe sepsis. Objective: Assess association of CgA levels and mortality risk of severely septic patients. Methods: Serum CgA levels were measured in 50 hospitalized, severely septic patients with organ failure <48 h. Results: Higher CgA levels trended toward higher ICU and hospital mortality. Patients without cardiovascular disease who died in the ICU had higher median (IQR) CgA levels 602.3 (343.3, 1134.3) ng/ml versus 205.5 (130.7, 325.9) ng/ml, p = 0.01. Conclusions: High CgA levels predict ICU mortality in severely septic patients without prior cardiovascular disease.